Composição do veneno de Loxosceles laeta peruana revelada por análise transcriptômica NGS e desenvolvimento da ferramenta computacional PepLess - Raissa Medina Santos (2021)
Accidents involving spiders of the Loxosceles genus are responsible for medical emergencies in several countries in South America. The species Loxosceles laeta is mainly found in Brazil and Peru, and it is responsible for an impressive number of accidents in those countries. To further characterize the components of the L. laeta venom and reveal possible variations in the particular Peruvian population, we provide an overview of the toxins present in the Peruvian L. laeta venom gland, using a cDNA library sequenced by the MiSeq sequencer (Illumina), and compared the data obtained with the transcriptome based on Expressed Sequence Tags (EST) of venom glands of Brazilian L. laeta from Fernandes-Pedrosa, 2008. The SPOT consists in the synthesis of a large number of peptides on a cellulose membrane, and it is a simple and low-cost tool for biotechnological applications and studies with large numbers of data, as is the case of the transcriptomic analysis of Peruvian L. laeta. Nevertheless, this technique becomes exhaustive when a large amount of sequences with different specifications is used, due to the extensive time taken to produce membranes and manual analysis of immunoassays, in addition to the excessive expenditure of materials and reagents. For these reasons, the PepLess tool was developed. It is an innovative device capable of selecting and analyzing a large number of sequences simultaneously, allowing a considerable reduction in the amount of membranes produced. With this system, it is possible to elaborate membranes with quality and specificity and automatically analyze the results obtained in the immunoassays. In this way, all the techniques that would previously be performed manually for the production and use of membranes for spot synthesis, can be automatic, fast and easy, allowing the generation of results with better efficiency and quality and transforming this technique into a powerful tool for complex analysis. To prove the efficiency and effectiveness of the tool, two case studies were used: The complete transcriptome analysis of Loxosceles laeta spiders of Peruvian origin and production of SPOT membrane with transcripts of the main Micrurus snakes present in South America.